Tobacco and Toil: A Narrative on Dependency on Tobacco Among Brick Workers - Gupta, Bhumika; Sharma, Swati; Ahmad, Faisal Noor; Tiwari, Sakchhi; Shankar, Shivangi; Manjul, Skand; Singh, Sushmita; Keshri, Suparna (Journal of Neonatal Surgery, 2025)
The global incidence of oral cancer has risen to 5%, but India’s share tells a grimmer story. India is bearing a disproportionate burden, representing 40% of the world's 60,000 annual new cases. The Human toll is devastating, clocking more than six deaths per hour, highlighting it’s deadly trajectory. Gautam Buddha Nagar’s chai stalls narrate mute tales – of cigarette-tough hands reaching for tobacco pouches rather than food; of lunch hours spent sucking on despair instead of sustenance. Here in India’s factory, fatigue gets rolled into bidi leaves and desperation chewed up with betel nut, one temporary relief at a permanent price. There is an inevitable link between oral cancer and tobacco, with the smokeless tobaccos, such as gutka and khaini, being especially malicious. In two, we found a silent pandemic of oral malignant disorders— smoker’s palate, OSMF & leukoplakia—each a precursor for a darker destiny. Smoker’s palate veils tissue devastation under its skeletal white appearance, while leukoplakia’s intransigent white spots portend an incipient malignancy. OSMF constricts its hold, converting soft tissue into an immovable cage, and erythroplakia, with its ominous red colour, is a silent killer, its cancerous change almost unavoidable. These are not merely ailments but signs, carved in flesh, disregarded at a deadly price. Despite measures to control tobacco, such as the Cigarettes and Other Tobacco Products Act (COTPA), poor enforcement, aggressive promotion, and entrenched cultural tolerance have hindered progress. The warnings are ignored, the risks unseen—until it is too late. In our periodic health camps at the brick kiln fields, we started to see the real extent of this disease. Among the mountains of freshly fired bricks, we saw workers whose mouths silently testified to years of addiction—white lesions, fibrotic tissues, and precancerous lesions speaking of a dark future. A survey of 188 labourer’s employed in brick kilns uncovered a starkly worrying reality. This article mines the depth of dependence among these workers, disentangling the complex interplay of social, economic, and psychological influences that trap them. It lays bare the failure of prevention, the complacency in early detection, and the almost insurmountable obstacles to treatment. The signals are present, etched into fate and flesh—signs not to be overlooked. The moment is not to do anything when cancer establishes itself, but when its first shadow is cast..